Analisis Kesulitan Belajar Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Barisan dan Deret Aritmatika - Masna, Masna; Ismail, Sumarno; Oroh, Franky A. (Scimadly Publishing, 2025)
This review aims to determine the learning difficulties experienced by class VIII students of SMP Negeri 2 Kwandang in understanding Groups and Mathematical Series which are estimated by signs of student learning difficulties. The strategy used is enlightening. The sampling procedure uses direct irregular examination, and the strategy for collecting information is to provide a trial of learning outcomes as an explanation that alludes to 3 signs of learning difficulties, namely calculated difficulty, guideline difficulty and functional challenge. The results showed that the level of students' learning difficulties was in the middle class. Many students were able to complete the narrative according to signs of learning difficulties. Students who have difficulty dealing with word problems due to a lack of understanding of the material and how to solve it. The lack of ability to answer questions and practice the material assisted requires techniques and systems to limit the difficulties experienced by students.